Faktor-faktor yang mempengaruhi kejadian kurang energi kronis (KEK) pada ibu hamil di wilayah kerja UPT Puskesmas I Pekutatan, Jembrana, Bali - Numbi Akhmadi Teguh; Ayu Hapsari; Putu Ria Asprila Dewi; Putu Aryani (Intisari Sains Medis, 2019)
Background: Common nutritional problems in pregnant women are chronic energy deficiency (CED). CED in pregnant women is a state of the mother lack of energy and protein intake during the period of pregnancy which can lead to the occurrence of health problems in the mother. This study aims to determine factors assoIKated with CED among pregnant women at UPT Puskesmas I Pekutatan, Jembrana, Bali.Methods: A case control study was conducted among 36 respondents, 12 cases (KEK) and 24 control (Non-KEK). The sampling technique used is purposive sampling technique. Affordable populations in this study were pregnant women recorded in medical records data at UPT Puskesmas I Pekutatan period 01 January-31 May 2017. The data were collected by interview using questionnaire and assessed using SPSS software version 20 for Windows. Existing data were analyzed by univariate and Fisher's exact bivariate with odds ratio calculation (OR).Results: About 13 respondents (36,1%) are <20 years old /> 35 years old with the most recent education is graduated from SMA that is 20 respondents (55,6%). Most respondents did not work (91.7%) and had low economic status (30.6%). Most of the respondents had children <2 (69.4%). Economic status (OR = 115; 95% IK: 9,3-1418), education level (OR = 2,3; 95% IK: 0,5-9,5), age (OR = 7,6; 95% IK: 1.6-35.9), gestational distance (OR = 11; 95% IK: 1.7-69), number of parities (OR = 7.6; 95% IK: 0.7-83.7) , And visit frequency of ANC (OR = 5; 95% IK: 0,9-26,4).Conclusion: The characteristic and frequency of ANC visit among pregnant women are risk factors of KEK occurrence in pregnant mother, so it is expected to provide information related to risk factors of KEK by health personnel in Puskesmas I Pekutatan, state of Jembrana.